Effects of Echinacea purpurea supplementation on markers of immunity, health, intake, and growth of dairy calves - B.K. McNeil; D.L. Renaud; M.A. Steele; A.J. Keunen; T.J. DeVries (Journal of Dairy Science, 2023)
ABSTRACT: Echinacea purpurea (EP) is an herb that has demonstrated immunostimulatory and anti-inflammatory effects with the potential to improve immunity, health, and performance in animals. The objective of this study was to investigate how supplementing calves with EP affects their blood immunity marker profile, health, intake, and growth. Male Holstein calves (n = 240), sourced from local dairy farms or auction, arrived at a rearing facility between 5 and 14 d of age and were kept in individual pens in 1 of 3 rooms (80/room) for 56 d, and then put into groups for the remaining 21 d of the trial. Calves received milk replacer (MR) 2× per day for 56 d (total = 36 kg of MR) and had ab libitum water and starter access. Within room, calves were randomly assigned to 1 of 3 treatments: (1) control (n = 80), (2) 3g of dried (powder) EP extract per day split over 2 milk feedings from experiment d 14–28 (n = 80), and (3) 3 g of dried (powder) EP extract per day split over 2 milk feedings from experiment d 1–56 (E56; n = 80). The powdered EP treatments were mixed into the liquid MR. On d 1, 14, 28, and 57 rectal temperatures and blood were collected from a subset of calves (n = 117; 39 calves/treatment), and blood serum was assessed for serum total protein (d 1), haptoglobin, white blood cells, and cytokines. Failed transfer of passive immunity was defined as serum total protein <5.2 g/dL. Calves were health scored 2× per day, receiving fecal and respiratory scores until d 28 and 77, respectively. Calves were weighed on arrival and then weekly until d 77. Milk replacer and feed refusals were recorded. Supplementation of EP was associated with lower haptoglobin levels, segmented neutrophil counts, segmented neutrophil per lymphocyte ratio, respiratory scores in auction derived calves, and higher lymphocyte counts and d 28 rectal temperature. Of calves with heavier arrival body weight, E56 calves had greater postweaning weekly body weight. There was no detected effect of EP supplementation on total white blood cells, band neutrophil, monocyte, and basophil counts, IL-10, IL-6, and TNF-α levels, fecal scores, risk of receiving diarrhea and respiratory treatment, risk of bovine respiratory disease (calves were deemed at risk for bovine respiratory disease if they had at least 1 respiratory score ≥5), risk of mortality, MR and feed intake, average daily gain, and feed conversion ratio. Overall, EP supplementation to dairy calves was associated with immunomodulation and reduced inflammation, evidenced through blood markers, although only few minor health and growth improvements were observed. Benefits were observed particularly when fed across the whole milk feeding period.